Effect Of Artificial Intelligence On The Strategies In Digital Marketing In The Field Of Business Administration - Makogonchuk, Olga (Digital Repository of Theses, 2025)
This paper examines the effects of artificial intelligence on the strategies in digital marketing in the field of digital marketing. This study looks at how AI improves data analytics, automates marketing processes, and optimizes customer experiences. The report identifies significant AI applications in digital marketing, such as chatbots, predictive analytics, and content creation tools, after conducting a thorough analysis of current literature, case studies, and industry examples. It also looks at the problems and ethical concerns involved with AI implementation in marketing. The findings demonstrate how AI-driven techniques improve efficiency, accuracy, and scalability, resulting in superior marketing outcomes. The thesis finishes with recommendations for marketers on how to properly use AI technology to remain competitive in the everchanging digital marketplace. It investigates the effects of artificial intelligence (AI) on digital marketing in the context of business administration. As AI technologies become increasingly integrated into business practices, their influence on digital marketing strategies is profound and multifaceted. The research delves into various AI applications, such as machine learning algorithms, predictive analytics, and automated content creation, to understand how they transform traditional marketing approaches. These technologies enable businesses to analyze vast amounts of data, leading to more precise customer segmentation, personalized marketing messages, and optimized campaign performance. The study highlights several key areas where AI impacts digital marketing: improving customer targeting through advanced data analysis, enhancing user experience with personalized content, and increasing the efficiency of marketing operations through automation. It also addresses potential challenges, including data privacy concerns and the need for businesses to adapt to rapidly evolving technology. The research contributes to a deeper understanding of how AI can be harnessed to drive innovation and competitiveness in the digital marketing landscape. Key words: Artificial Intelligence, Digital Marketing, Business Administration, Predictive Modeling, Chatbots, Customer Engagement, Targeted Advertising, Automated, Strategies, bias on AI